EFFECT OF DISCIPLINE AND ENVIRONMENTAL FAMILY LEARNING ON THE ACHIEVEMENT CLASS 6 SD MUHAMMADIYAH KAMPUNGSEWU 2015 / 2016 - KINASIH, AYU ROHMAH (2016)
ABSTRACT AyuRohmahKinasih / A510120149. EFFECT OF DISCIPLINE AND ENVIRONMENTAL FAMILY LEARNING ON THE ACHIEVEMENT CLASS 6 SD MUHAMMADIYAH KAMPUNGSEWU 2015 / 2016. Thesis. The Faculty of Education, University of Muhammadiyah Surakarta. January, 2016. This study aims to determine: (1) the effect of the discipline of learning on student achievement upscale SD Muhammadiyah 6 Kampungsewu, (2) the influence of family environment on student achievement upscale SD Muhammadiyah 6 Kampungsewu, (3) the effect of learning discipline and the family environment on student achievement upscale SD Muhammadiyah 6 Kampungsewu. This research is quantitative research. The study population was all students in grade IV, V, VI SD Muhammadiyah 6 Kampungsewu Year 2015/2016. Data collection techniques are questionnaires and dokumentasi.Teknik testing instrument covers the validity and reliability test. Data analysis technique used is multiple regression, t test, F test, the coefficient of determination and SR and SE. Data. Results of regression analysis regression line equation: Y = 23,697+ 0,279X1 + 0,276X2. T test results obtained and t_hitungt_hitung = 2.696 = 2.774. While the test results obtained F_hitung F = 24.572. From the analysis, it can be stated that: (1) the discipline of learning positive and significant impact on student achievement with (2) a family environment positive and significant impact on student achievement with (3) the discipline of learning and family environment positive and significant impact on achievement student learning. The relative contribution of the discipline learned by 49.28% and 50.85% of the family environment. Effective contribution to the discipline of learning by 23.45% while the family environment of 24.20%. The rest is influenced by other variables not studied. Keywords: discipline, learning, environment, family, achievement, learning